2015
DOI: 10.1088/0031-8949/90/3/035103
|View full text |Cite
|
Sign up to set email alerts
|

Quantum correlations of three-qubit states driven by a classical random external field

Abstract: In this paper, we exploit the notions of tripartite quantum discord  (3) , tripartite negativity  (3) , and entanglement witnesses (EWs), respectively, as a measure of quantum correlations in a model of three noninteracting qubits subject to a classical random external field. We compare the dynamics of  (3) with that of entanglement for the initial entangled pure or mixed GHZ-and W-type states. We find that the quantum correlations dynamics depend on the input configuration of the purity of the initial stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…And their decay will be independent decay. This case can be solved analytically, as we and other authors have done before 1 , 32 34 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…And their decay will be independent decay. This case can be solved analytically, as we and other authors have done before 1 , 32 34 .…”
Section: Resultsmentioning
confidence: 96%
“…In 2010, based on Agarwal’s PNLs model 20 , 21 , 25 , 30 , and by using the Zwanzig–Nakajima projection operator technique, J.D.Cresser derived a master equation without a stochastic variable 31 . After that, there are some researchers studied the physical problems on PNLs with this J.D.Cresser’s master equation, such as QFI 1 , 32 , the discord of two-qubit X state 33 , and the discord and the entanglement of three-qubit GHZ state and W state 34 . Although they investigated multi-atom PNLs problems by using this master equation, their calculations are with no interactions between atoms and no spontaneous emissions, and do not focus on more complicated problems with d – d interactions and collective decay (or cooperative emission) of multiple atoms when the atoms are much closer to each other.…”
Section: Introductionmentioning
confidence: 99%
“…where I i jk represents the identity matrix acting on the Hilbert space of the qubits i, j and k and ℋ s , s = a, b, c, d stands for the single qubit-field Hamiltonian which can be written in the rotating frame at the qubit-field resonant frequency ω as [24,28] ℋ s (t) = i hg σ + e −iφ s i − σ − e iφ s i .…”
Section: Theoretical Methods 21 Physical Modelmentioning
confidence: 99%
“…They also showed that in such an environment, quantum correlations do not vanish any more when the probabilities of the field phase range from 0.5 to 1 (the behavior is symmetric with respect to 0.5). Furthermore, in 2015 the dynamic of quantum correlations of three-qubit states driven by a CREF has been studied by Guo et al [28] and their results show that tripartite quantum discord may be more robust than entanglement under such a classical environment. They also showed that under this classical field, entanglement displays periodically sudden death and revivals for GHZ-and W-type states and that the survival partial entanglement can be detected employing suitable entanglement witness operators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation